PELAYANAN DAN PENERAPAN BUKU SAKU BRAILLE KESEHATAN GIGI DALAM MENURUNKAN ANGKA KARIES GIGI DAN SKOR DEBRIS INDEKS PADA ANAK PANTI SOSIAL TUNA NETRA FAJAR HARAPAN - Waljuni, Waljuni Astu Rahman; habibah, Siti Sab'atul habibah, SKM, M.Kes; Danan, Danan, S.Si.T, M.Kes (UPPM Poltekkes Kemenkes Banjarmasin, 2026)
Visually impaired children are individuals who experience abnormalities in their sense of sight, causing their eyes to function abnormally. These children are among those with special needs who require specific services, both in education and health. To address this issue, the application of a Braille dental health pocketbook serves as an educational medium and an assistive tool to develop toothbrushing skills among visually impaired children. Health Transformation In the context of health system transformation, the first pillar often relates to efforts to improve access to and coverage of quality health services. The implementation of the Braille dental health pocketbook as a media-based assistive tool for toothbrushing skills in visually impaired children can help increase public access to health information and services related to oral health issues, supporting the mission of Indonesia Free from Dental Caries by 2030. Through this educational initiative, visually impaired children can more easily and effectively learn how to maintain oral hygiene and practice proper toothbrushing techniques. The use of the Braille dental health pocketbook as an assistive media tool for developing toothbrushing skills among visually impaired children also encourages active participation in addressing oral health problems. Through interactive approaches or platforms, visually impaired children can engage in monitoring their oral hygiene, sharing experiences, and exchanging knowledge. This helps to increase awareness of the importance of their active role in maintaining oral and dental health. By utilizing the Braille dental health pocketbook as a media-based assistive tool for toothbrushing skills among visually impaired children, it is possible to optimize resource use within the health system. The use of interactive media and models can enhance the efficiency of oral health awareness. Furthermore, this model can be used to improve the planning and management of oral health programs for children with special needs more effectively.